Interview with Raphaël Nkaka, Rwandan historian - (:unkn) unknown (My University, 2022)
This interview is the result of exchanges that began in the summer of 2018 in Rwanda between two researchers specializing in Central Africa. It gives us the opportunity to discover the trajectory of a Rwandan historian, Raphaël Nkaka, whose intellectual journey between Europe and Africa, is part of the traumatic history of his country of origin and in particular the Tutsi genocide (April to July 1994). It also offers the opportunity to discover his work and the authors or personalities who have influenced him.
Keywords: African Research